Claude Charles Bloch papers - Bloch, Claude Charles, 1878-1967.
Correspondence, journal (1934) kept by Bloch as judge advocate general of the U.S. Navy, subject file, and miscellaneous material relating chiefly to Bloch's activities as commander in chief of the U.S. Fleet (1938-1940) and commandant of the 14th Naval District, Pearl Harbor (1940-1942). Correspondents include Charles A. Edison, James Forrestal, Ernest L. Jahncke, Hiram Johnson, Frank Knox, William D. Leahy, Chester W. Nimitz, David Sarnoff, Harold R. Stark, Claude Augustus Swanson, Burton K. Wheeler, and Harry Hines Woodring.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Edison, Charles A., -- 1890-1969 -- Correspondence; Forrestal, James, -- 1892-1949 -- Correspondence; Jahncke, Ernest L. -- 1877-1960 -- Correspondence; Johnson, Hiram, -- 1866-1945 -- Correspondence; Knox, Frank, -- 1874-1944 -- Correspondence; Leahy, William D. -- Correspondence; Nimitz, Chester W. -- 1885-1966 -- Correspondence; Sarnoff, David, -- 1891-1971 -- Correspondence; Stark, Harold R. -- 1880-1972 -- Correspondence; Swanson, Claude Augustus, -- 1862-1939 -- Correspondence; Wheeler, Burton K. -- 1882-1975 -- Correspondence; Woodring, Harry Hines, -- 1887-1967 -- Correspondence; United States. -- Navy; United States. -- Navy. -- Naval District, 14th.; United States. -- Navy. -- Office of the Judge Advocate General; Naval districts -- United States; Navy-yards and naval stations -- Hawaii -- Pearl Harbor; Pearl Harbor (Hawaii), Attack on, 1941.; World War, 1939-1945 -- Naval operations, American; Naval officers